Shifting Cultivation and Secondary Succession in the Tropics - Aweto, Albert O (CABI, 2014)
Shifting cultivation, involving rotational fallowing, is the dominant system of arable farming in the humid and sub-humid tropics, where the bulk of the total food output is produced by small-scale farmers, the majority of whom are shifting cultivators. The system of agriculture is, therefore, vital to food security and to meeting the Millennium Development Goal of reducing hunger and malnutrition in most tropical countries. The system of shifting cultivation is an ecologically sound and ef ective strategy of arable land management, especially in areas where rural population density is low, as it depends on the natural processes of organic matter and nutrient cycling to restore the fertility of soils which declined during cropping. In the wake of rapid population increase in the tropics, particularly during the last two to ﬁ ve decades, fallow periods have been considerably shortened and the system of shifting cultivation is breaking down and becoming unsustainable. This brings to the fore the need to study the system of shifting cultivation in order to intensify it in an ecologically sound and sustainable manner, or replace it – where ecological, pedological and sociological conditions permit – with a more intensive system of farming. Several books and journal articles have been published on the subject of shifting cultivation, particularly since 1960 when Nye and Greenland published their seminal book, The Soil Under Shifting Cultivation. 1 It is pertinent to observe that such books or journal articles are area- speciﬁ c, concentrating on particular countries or regions, or even on cultural practices by certain ethnic groups. This has tended to hinder a holistic and pan-tropical understanding of the system of shifting cultivation. It is also signiﬁ cant to note that published works on shifting cultivation, including recent works of the past 5 years or so, are scattered in a multiplicity of sources, including several scores of dif erent journals. The present book attempts to document and systematize ﬁ ndings on shifting cultivation on a pan-tropical basis, drawing on major ﬁ ndings in the literature in the last ﬁ ve decades. This book adopts a novel, perhaps even a unique approach. Most published research works on the subject have adopted a dichotomous methodology to the study of shifting cultivation, in which the soil and vegetation components of the bush fallow ecosystem are considered independently of one another. Foresters and ecologists have tended to focus primarily on the nature, composition, and dynamics of fallow vegetation; that is, secondary succession, without quantitatively characterizing the soils underneath fallow vegetation. In contrast, agronomists have tended to focus primarily on fallow soil dynamics, and hence on the process of soil fertility restoration during the fallow period, without matching soil changes with changes in fallow vegetation. The current book examines the processes of secondary succession and soil fertility restoration under bush fallow within an integrative framework. It goes beyond merely juxtaposing the discourse on secondary succession and the process of soil fertility restoration in bush fallow, and adopts a soil–vegetation system approach to the study of the bush fallow. This approach recognizes that the soil and vegetation components of the bush fallow – an important component of the shifting cultivation cycle – as open and interdependent systems which exert reciprocal ef ects on one another. The interrelationships between fallow soil and vegetation are explored using simple bivariate correlations and stepwise multiple regression, drawing mainly on the author’s work in south-western Nigeria, although reference is also made to published works in South America. This approach made it possible to identify the salient characteristics of fallow vegetation which enhance the process of soil fertility restoration under bush fallow, and those of fallow soil which enhance the regeneration of fallow vegetation.